Effects of guanidinoacetic acid on antioxidant status, inflammation and growth performance of broilers under cool temperature and excessive salt-induced ascites : GAA and ascites - Fathi, M; Saeedyan, S; Nuraddin Mohammed , H; Zarrin Kavyani, K; Rezaee , V (Journal of the Hellenic Veterinary Medical Society, 2025)
The study was carried out to investigate the effect of dietary guanidinoacetic acid (GAA) on performance of growth, biochemical parameters, and antioxidant capacity also cytokine responses in broiler chickens subjected to cold stress. Total of 200, day-old male Ross-308 broilers were randomly distributed into four dietary treatments with five replication pens, each pen had 10 broilers. All birds were investigated to cool temperatures environment in combination with excess salt in their drinking water to induce ascites and received basal diet supplemented with different levels of guanidinoacetic acid (GAA) at the levels of (0, control; GAA1, 0.10%; GAA2, 0.20% and GAA3, 0.30%) from 16 to 42 days of age. On day 42, two birds per each cage were weighed and euthanized, and samples were collected. Results showed higher body weight gain & feed intake and lower Ascites mortality & RV/TV index in (GAA2 and GAA3) groups. Also, serum creatine kinase (CK) activity, cholesterol, triglycerides, Nitric oxide and creatinine levels showed a marked significant (P<0.05) increase in (GAA2 and GAA3) groups supplemented groups compared to the other groups. Lipid peroxidation marker (Malondialdehyde/MDA) is showed decreased with a significant increase of glutathione peroxidase (GPx) in serum and liver, and catalase (CAT) in serum in both (GAA2 and GAA3) compared to other groups. Similarly, GAA supplementation in both (GAA2 and GAA3) groups enhanced the interleukin (IL) -10 level and reduced the, tumor necrosis factor (TNF)-α and IL -1β serum and liver than broilers in the other groups. No significant effect appeared in other biochemical parameters (P>0.05). In conclusion, dietary GAA supplementation can alleviate Ascites-induced oxidative stress also inflammation response by decreasing lipid peroxidation, TNF-α and IL-1β and increasing antioxidant function and IL-10 level in broiler chickens.